Effect of different palatal vault shapes and woven glass fiber reinforcement on dimensional stability of high impact acrylic denture base [part II] - Shnay M Atiyah; Thekra I Hamad (College of Dentistry/ University of Baghdad, 2015)
Background: Change in palatal vault shape and Reinforcement of high impact acrylic denture base resin may in turn affect the dimensional accuracy of acrylic resin and affecting the fitness of the denture. The aim of study is to evaluate the effect of fiber reinforcement for high-impact acrylic resin denture base with different palatal vault shapes on linear dimensional change and effect of palatal vault shapes on linear dimensional changes of non-reinforced and fiber reinforced high impact denture base acrylic resin Material and method: Three different palatal vault shapes were prepared on standard casts using CNC (computer numerical control) machine. 60 samples of heat polymerized high impact acrylic resin maxillary denture base were fabricated onto each definitive cast according to manufacturer instruction. Samples divided into three main experimental groups represented the three different palatal vault shapes (20 samples for each main group); 1st rounded 2nd U-shaped and the 3rd groups V-shaped. Each main group divided into two subgroups (10 samples for each subgroup) representing non fiber reinforced high impact acrylic group as a control and the fiber reinforced high impact acrylic. The measurements of linear dimensional changes of denture bases done at two stages, 1st 24 hour after polymerization and 2nd measurement done after one month storage in distilled water at room temperature. Results and conclusion: Linear dimensional changes of high impact acrylic denture base not affected by glass fiber reinforcement p-value in all reference lines ≥ 0.05, while topographical change in maxillary vault shapes effects on the linear dimensional changes in woven glass fiber reinforced high impact acrylic denture base p-value < 0.05. Key words: High impact acrylic resin, topographical change in vault, woven glass fiber reinforcement.